A META-ANALYSIS OF THE SOFT TISSUE DEFECTS CLASSIFICATION AND JUSTIFICATION OF THE OPTIMAL SURGICAL RECONSTRUCTION METHOD - Tertyshnyi, Sergiy; Khomenko, Igor; Gumenyuk Кostyantyn; Korol, Sergiy; Tsema, Yevgen; Dubenko, Dmytro; Mikhaylusov, Rostyslav; Grinchuk, Mykola; Popova, Oksana (The Ukrainian Scientific Medical Youth Journal, 2021)
During the military conflict in the East of Ukraine, considerable experience in providing medical assistance to wounded and in- jured with soft tissue defects has been accumulated. Taking into account the considerable diversity of defects of soft tissues on numerous a number of signs, which involves the application in the process of treatment of fundamentally different algorithms of preoperative training, planning of reconstructive intervention and method of surgical reconstruction there was a need to systematize the accumulated knowledge by developing the integral classification of soft tissue defects.